2022
DOI: 10.2196/31456
|View full text |Cite
|
Sign up to set email alerts
|

Digital Interventions for Emotion Regulation in Children and Early Adolescents: Systematic Review and Meta-analysis

Abstract: Background Difficulties in emotion regulation are common in adolescence and are associated with poor social and mental health outcomes. However, psychological therapies that promote adaptive emotion regulation may be inaccessible and unattractive to youth. Digital interventions may help address this need. Objective The aim of this systematic review and meta-analysis was to synthesize evidence on the efficacy, feasibility, and acceptability of emotion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 149 publications
1
16
0
Order By: Relevance
“…Emotion regulation skills are key components of empirically-supported treatments for psychopathology [25,26] and have been shown to mediate and moderate effects of interventions on outcomes [24]. Increasingly, emotion regulation skills have been incorporated into digital health interventions [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Emotion regulation skills are key components of empirically-supported treatments for psychopathology [25,26] and have been shown to mediate and moderate effects of interventions on outcomes [24]. Increasingly, emotion regulation skills have been incorporated into digital health interventions [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Further, much of the research to date has focused on the delivery of such interventions in person despite a growing number of digital solutions for adolescent emotion regulation and psychopathology 23. Previous research examining the effectiveness of several different digital interventions targeting emotion regulation in adolescents found that, in general, such interventions (eg, digital games and biofeedback) can be effective in improving emotion regulation 29. Digital interventions also have a greater capacity for innovation and engagement with adolescents30 and the potential to extend effective care cost-effectively and sustainably,31 but less is known about how such interventions can be applied at scale to support this population.…”
Section: Introductionmentioning
confidence: 99%
“…Despite an increase in the number of available self-directed digital interventions for emotion regulation, evidence about their effectiveness among adolescent populations has yet to be synthesised. This review provides an important extension to existing work which has thus far demonstrated the effectiveness of in-person or therapist-supported emotion regulation interventions available for young people (aged 6–24 years),20 as well as the utility of a broad spectrum of digital emotion regulation interventions for adolescents 29. This review takes a more specific focus to develop evidence on a burgeoning number of self-directed , scalable, digital mental health interventions available to adolescents with or without diagnosed psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature demonstrated the efficacy of interventions devoted to enhancing socio‐emotional skills in children and adolescents (Durlak et al, 2022), also through digital interventions (Reynard et al, 2022). However, little research has been focussed on evidence‐based programmes aimed at increasing emotional competence as a key resource to cope with disasters.…”
Section: Introductionmentioning
confidence: 99%